Анализ методов и средств «раскрутки» сайтов в Интернете - Валькман, Ю.Р.; Зосимов, В.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
The processes of information retrieval are explored in a network the Internet.
Attention is accented on methods and facilities of optimization of sites in a network the Internet. The system of estimation of efficiency of optimization of site is developed.